Electrodeposition of Ag onto Au(111) from Deep Eutectic Solvents. Issue 1 (30th November 2018) - Ceblin, Maximilian U.; Zeller, Sven; Schick, Benjamin; Kibler, Ludwig A.; Jacob, Timo
Abstract: Silver electrodeposition onto Au(111) has been studied as a function of composition of deep eutectic solvent (DES) type III and IV. The electrochemical investigations were performed by using cyclic voltammetry and in‐situ electrochemical quartz crystal microbalance experiments. Scanning electron microscopy coupled with Auger spectroscopy and atomic force microscopy were used to characterize the deposited metal overlayers. Silver deposition from DES type III shows several analogies to the electrocrystallization from aqueous solutions, such as the presence of underpotential deposition. It is shown that the hydrogen‐bond donor exerts a strong influence on the silver growth mode and on the structure of the metal deposits. In addition, the hydrogen‐bond donor turns out to exert a rather strong influence on the plating process during silver deposition from DES type IV. Abstract : Improved electrolytes : The first study to characterize the galvanic deposition of silver from a type IV deep eutectic solvent. The growth of a silver film on Au(111) was investigated by using various electrochemical methods. This class of electrolyte has promising properties that can be used in electroplating and battery technologies. In particular, this class of electrolyte might provide an appealing alternative to common ionic liquids for the electrocrystallization of reactive metals.